Answer:
The inverse function of 3x - 4 is (x+4)/3. so a
Step-by-step explanation:
f(x) = 3x - 4
y = 3x - 4 replace f(x) with y
x = 3y - 4 replace x with y and y with x.
3y = x + 4 solve for y
y = (x+4)/3 replace y with f-1(x)
f-1(x) = (x+4)/3
10 2/6= Becomes 9 8/6
-21/2= 3/6. -2 3/6
Answer 7 5/6 tons
6 • x + 6 • 9
I’m pretty sure this is right because you have to distribute the 6 to both of the numbers inside of the parentheses
Answer:
A. (x,y) → (-x,y)
Step-by-step explanation:
A: (-5,-1)
A': (5,1)
B: (-3, -3)
B': (3, -3)
C: (-5, -5)
C': (5, -5)
D: (-7, -3)
D': (7,-3)
The x values change sign but the y values don't.
The answer is 5.25%.
$65,625/10yrs=$6,562.50 per a year.
6,562.5/125000= .0525 which translates to 5.25%.